2015
DOI: 10.1371/journal.pone.0136328
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Monoclonal Antibodies against Dengue Virus Type 4 and Identification of Enhancing Epitopes on Envelope Protein

Abstract: The four serotypes of dengue virus (DENV1-4) pose a serious threat to global health. Cross-reactive and non-neutralizing antibodies enhance viral infection, thereby exacerbating the disease via antibody-dependent enhancement (ADE). Studying the epitopes targeted by these enhancing antibodies would improve the immune responses against DENV infection. In order to investigate the roles of antibodies in the pathogenesis of dengue, we generated a panel of 16 new monoclonal antibodies (mAbs) against DENV4. Using pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 44 publications
0
19
0
1
Order By: Relevance
“…Arg9 and Glu13 are also epitopes of other antibodies 35 . This particular study also showed that the N8R substitution DNA vaccine had a more neutralizing and protective effect than wild-type immunized sera, both in vitro and in vivo 35 . Arg9 is part of a salt bridge with Glu368 which maintains the structure of the E-protein in the pre-fusion state 10, 64 .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Arg9 and Glu13 are also epitopes of other antibodies 35 . This particular study also showed that the N8R substitution DNA vaccine had a more neutralizing and protective effect than wild-type immunized sera, both in vitro and in vivo 35 . Arg9 is part of a salt bridge with Glu368 which maintains the structure of the E-protein in the pre-fusion state 10, 64 .…”
Section: Resultsmentioning
confidence: 99%
“…Tyr299 is part of the epitope for the cross-reactive neutralizing MAb DENV1-E102 66 . Arg188 is essential for infectivity, and is neutralized by DC4 Fab 40 , while the monoclonal antibody DD18-5 recognized residue Glu26 in DENV4 35 , a residue predicted by the Pepitope server 34 . Thus, all spatially perturbed residues identified by MEPP are known epitopes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from vaccines, other anti-viral strategies include developing peptide vaccines 28 , using peptide-inhibitors derived from the viral proteins 29 , inhibiting the fusion process 30 and anionic peptides that target cationic ‘hotspots’ 31 , 32 . Computational epitope predictors like the sequence based RANKpep 33 or the structure based Pepitope 34 have been used to validate antibody binding 35 , 36 . A detailed structural analysis of proteins of these flaviviruses will provide deeper insight into conservation than a sequential analysis does.…”
Section: Introductionmentioning
confidence: 99%
“…Geralmente, um sorotipo de dengue é dominante por um período de dois a seis anos, após o qual ele sofre um declínio na prevalência quando um sorotipo diferente emerge para substituí-lo (Adams et al 2006;Rabaa et al 2010) (Morens et al1985;Thomas et al 2009;Timiryasova et al 2013;Sirivichayakul et al 2014;Salje, et al 2014;Tang et al 2015) que, as reações cruzadas observadas refletem nos períodos das epidemias (Adams et al 2006).…”
Section: Ensaio Neutralização De Reação-cruzadaunclassified